Exploring physical activity and patient perceptions in knee osteoarthritis: A mixed-methods study - Moayad Subahi; Fahda Alshaikh; Eyad Dahlawi; Feras Zafar; Tamim Alsulimany; Nawaf Alnefaie; Abdulrahman Almalki (PLoS ONE, 2025)
Knee osteoarthritis (KOA) is a prevalent condition that reduces physical function and quality of life. Physical activity is foundational to KOA management; however, patient engagement and perceptions of treatment remain underexplored, particularly in Middle Eastern populations. This study evaluated physical activity (PA) levels among individuals with KOA and explored their perceptions, awareness, and experiences with management strategies, especially physical therapy. A sequential explanatory mixed-methods design was employed. Quantitative data were collected using the International Physical Activity Questionnaire-Short Form (IPAQ-SF) from 60 adults with physician-diagnosed KOA (mean age 55.5 ± 6.4 years; 50% female) recruited from clinics and community programs in Saudi Arabia. Semi-structured interviews with 24 purposively selected participants further explored experiences and perceptions. Descriptive statistics summarized quantitative data, and thematic analysis guided qualitative interpretation. Ninety percent of participants recorded low PA levels (≤600 MET-min/week), with only 10% achieving moderate or high activity levels. Qualitative themes revealed multiple barriers including emotional distress, logistical difficulties, and misconceptions about KOA as well as facilitators such as family support and patient education. Integration of findings highlighted how contextual and psychosocial factors influence PA engagement. Adults with KOA in this study reported markedly low levels of PA, shaped by cultural, psychological, and environmental factors. Our findings highlight the importance of addressing these barriers through patient-centred education and improved access to physical therapy.